Regulation essential to curb AI for surveillance, disinformation: rights experts - UN News (UN News, 2023)
Artificial intelligence (AI)-powered spyware and disinformation is on the rise, and regulation of the space has become urgent, according to UN-appointed independent rights experts.
Worldwide
Keywords: 2023-06 June